Next: Exercises
Up: Ellipsoidal Potential Theory
Previous: Introduction
Consider the contribution to the potential at
from the mass contained within a double cone, whose apex
is
, and which is terminated in both directions at the body's outer boundary. (See Figure D.1.)
If the cone subtends a solid angle
then a volume element is written
, where
measures displacement from
along the axis of the cone. Thus, from standard classical gravitational theory (Fitzpatrick 2012), the
contribution to the potential takes the form
![$\displaystyle d{\mit\Psi} = - \int_0^{r'}\frac{G\,\rho}{r}\,dV - \int_{r''}^0 \frac{G\,\rho}{(-r)}\,dV,$](img7229.png) |
(D.2) |
where
,
, and
is the constant mass density of the ellipsoid. Hence, we obtain
![$\displaystyle d{\mit\Psi} = -G\,\rho\left(\int_0^{r'} r\,dr + \int_0^{r''} r\,d...
...ght)d{\mit\Omega} =- \frac{1}{2}\,G\,\rho\,(r'^{\,2}+r''^{\,2})\,d{\mit\Omega}.$](img7232.png) |
(D.3) |
The net potential at
is obtained by integrating over all solid angle, and dividing the result by two to adjust for
double counting. This yields
![$\displaystyle {\mit\Psi} = - \frac{1}{4}\,G\,\rho\oint \,(r'^{\,2}+r''^{\,2})\,d{\mit\Omega}.$](img7233.png) |
(D.4) |
Figure D.1:
Calculation of ellipsoidal gravitational potential.
![\begin{figure}
\epsfysize =2.25in
\centerline{\epsffile{AppendixD/fig5.06.eps}}
\end{figure}](img7234.png) |
From Figure D.1, the position vector of point
, relative to the origin,
, is
![$\displaystyle {\bf x}' = {\bf x} + r'\,{\bf n},$](img7235.png) |
(D.5) |
where
is the position vector of point
, and
a unit vector pointing from
to
. Likewise, the position vector of point
is
![$\displaystyle {\bf x}'' = {\bf x} + r''\,{\bf n}.$](img7236.png) |
(D.6) |
However,
and
both lie on the body's outer boundary. It follows, from Equation (D.1), that
and
are
the two roots of
![$\displaystyle \sum_{i=1,3}\left(\frac{x_i+r\,n_i}{a_i}\right)^2=1,$](img7237.png) |
(D.7) |
which reduces to the quadratic
![$\displaystyle A\,r^{\,2}+ B\,r+C = 0,$](img7238.png) |
(D.8) |
where
According to standard polynomial equation theory (Riley 1974),
, and
. Thus,
![$\displaystyle r'^{\,2}+r''^{\,2} = (r'+r'')^2- 2\,r'\,r'' = \frac{B^{\,2}}{A^2} - 2\,\frac{C}{A},$](img7245.png) |
(D.12) |
and Equation (D.4) becomes
![$\displaystyle {\mit\Psi} = -\frac{1}{2}\,G\,\rho\oint\left[ \frac{2\left(\sum_{...
...,3}x_i^{\,2}/a_i^{\,2}}{\sum_{i=1,3}n_i^{\,2}/a_i^{\,2}} \right] d{\mit\Omega}.$](img7246.png) |
(D.13) |
The previous expression can also be written
![$\displaystyle {\mit\Psi} = -\frac{1}{2}\,G\,\rho\oint\left[ \frac{2\sum_{i,j=1,...
...,3}x_i^{\,2}/a_i^{\,2}}{\sum_{i=1,3}n_i^{\,2}/a_i^{\,2}} \right] d{\mit\Omega}.$](img7247.png) |
(D.14) |
However, the cross terms (i.e.,
) integrate to zero by symmetry, and we are left with
![$\displaystyle {\mit\Psi} = -\frac{1}{2}\,G\,\rho\oint\left[ \frac{2\sum_{i=1,3}...
...,3}x_i^{\,2}/a_i^{\,2}}{\sum_{i=1,3}n_i^{\,2}/a_i^{\,2}} \right] d{\mit\Omega}.$](img7249.png) |
(D.15) |
Let
![$\displaystyle J = \oint \frac{d{\mit\Omega}}{\sum_{i=1,3}n_i^{\,2}/a_i^{\,2}}.$](img7250.png) |
(D.16) |
It follows that
![$\displaystyle \frac{1}{a_i}\,\frac{\partial J}{\partial a_i} = \oint\frac{2\,n_...
...,2}/a_i^{\,4}}{\left(\sum_{i=1,3} n_i^{\,2}/a_i^{\,2}\right)^2}\,d{\mit\Omega}.$](img7251.png) |
(D.17) |
Thus, Equation (D.15) can be written
![$\displaystyle {\mit\Psi} = - \frac{1}{2}\,G\,\rho\left(J - \sum_{i=1,3}\,A_i\,x_i^{\,2}\right),$](img7252.png) |
(D.18) |
where
![$\displaystyle A_i = \frac{J}{a_i^{\,2}}-\frac{1}{a_i}\,\frac{\partial J}{\partial a_i}.$](img7253.png) |
(D.19) |
At this stage, it is convenient to adopt the spherical angular coordinates,
and
(see Section C.4), in terms of which
![$\displaystyle {\bf n} = (\sin\theta\,\cos\phi,\,\sin\theta\,\sin\phi,\,\cos\theta),$](img7254.png) |
(D.20) |
and
. We find, from Equation (D.16), that
![$\displaystyle J= 8\int_0^{\pi/2}\sin\theta\,d\theta\int_0^{\pi/2}\left(\frac{\s...
...theta\,\sin^2\phi}{a_2^{\,2}}+ \frac{\cos^2\theta}{a_3^{\,2}}\right)^{-1}d\phi.$](img7255.png) |
(D.21) |
Let
. It follows that
![$\displaystyle J = 8\int_0^{\pi/2}\sin\theta\,d\theta \int_0^\infty \frac{dt}{a+b\,t^2} = 4\pi\int_0^{\pi/2}\frac{\sin\theta\,d\theta}{(a\,b)^{1/2}},$](img7257.png) |
(D.22) |
where
Hence, we obtain
![$\displaystyle J = 4\pi\,a_1\,a_2\,a_3^{\,2}\int_0^{\pi/2}\frac{\sin\theta\,\sec...
...2}+a_3^{\,2}\,\tan^2\theta)^{1/2}\, (a_2^{\,2}+a_3^{\,2}\,\tan^2\theta)^{1/2}}.$](img7260.png) |
(D.25) |
Let
. It follows that
![$\displaystyle J = 2\pi\,a_1\,a_2\,a_3\int_0^\infty \frac{du}{\mit\Delta},$](img7262.png) |
(D.26) |
where
![$\displaystyle {\mit\Delta} = (a_1^{\,2}+u)^{1/2}\,(a_2^{\,2}+u)^{1/2}\,(a_3^{\,2}+u)^{1/2}.$](img7263.png) |
(D.27) |
Now, from Equations (D.19), (D.26), and (D.27),
Thus, Equations (D.18), (D.26), and (D.28) yield
![$\displaystyle {\mit\Psi} = - \frac{3}{4}\,G\,M\left(\alpha_0-\sum_{i=1,3}\alpha_i\,x_i^{\,2}\right),$](img857.png) |
(D.29) |
where
Here,
and
are the body's mass and volume, respectively.
The total gravitational potential energy of the body is written (Fitzpatrick 2012)
![$\displaystyle U = \frac{1}{2}\,\int{\mit\Psi}\,\rho\,dV,$](img7270.png) |
(D.32) |
where the integral is taken over all interior points. It follows from Equation (D.29) that
![$\displaystyle U = -\frac{3}{8}\,G\,M^{\,2}\left(\alpha_0 - \frac{1}{5}\,\sum_{i=1,3}\alpha_i\,a_i^{\,2}\right).$](img7271.png) |
(D.33) |
In writing the previous expression, use has been made of the easily demonstrated result
.
Now,
![$\displaystyle 2\,\frac{d}{du}\!\left(\frac{u}{\mit\Delta}\right) = -\frac{1}{\mit\Delta}+ \sum_{i=1,3}\frac{a_i^{\,2}}{(a_i^{\,2}+u)\,{\mit\Delta}},$](img7273.png) |
(D.34) |
so
![$\displaystyle \sum_{i=1,3}\alpha_i\,a_i^{\,2} = \int_0^\infty \sum_{i=1,3}\frac...
...u}\!\left(\frac{u}{\mit\Delta}\right)+\frac{1}{\mit\Delta}\right]du = \alpha_0.$](img7274.png) |
(D.35) |
Hence, we obtain
![$\displaystyle U =-\frac{3}{10}\,G\,M^{\,2}\,\alpha_0.$](img869.png) |
(D.36) |
Next: Exercises
Up: Ellipsoidal Potential Theory
Previous: Introduction
Richard Fitzpatrick
2016-01-22